Whole-exome sequencing identifies MDH2 as a new familial paraganglioma gene - Cascón, Alberto; Comino-Méndez, Iñaki; Currás-Freixes, María; de Cubas, Aguirre A; Contreras, Laura; Richter, Susan; Peitzsch, Mirko; Mancikova, Veronika; Inglada-Pérez, Lucía; Pérez-Barrios, Andrés; Calatayud, María; Azriel, Sharona; et al. (JNCI : Journal of the National Cancer Institute, 2015)
Disruption of the Krebs cycle is a hallmark of cancer. IDH1 and IDH2 mutations are found in many neoplasms, and germline alterations in SDH genes and FH predispose to pheochromocytoma/paraganglioma and other cancers. We describe a paraganglioma family carrying a germline mutation in MDH2, which encodes a Krebs cycle enzyme. Whole-exome sequencing was applied to tumor DNA obtained from a man age 55 years diagnosed with multiple malignant paragangliomas. Data were analyzed with the two-sided Student's t and Mann-Whitney U tests with Bonferroni correction for multiple comparisons. Between six- and 14-fold lower levels of MDH2 expression were observed in MDH2-mutated tumors compared with control patients. Knockdown (KD) of MDH2 in HeLa cells by shRNA triggered the accumulation of both malate (mean ± SD: wild-type [WT] = 1±0.18; KD = 2.24±0.17, P = .043) and fumarate (WT = 1±0.06; KD = 2.6±0.25, P = .033), which was reversed by transient introduction of WT MDH2 cDNA. Segregation of the mutation with disease and absence of MDH2 in mutated tumors revealed MDH2 as a novel pheochromocytoma/paraganglioma susceptibility gene.